Analysis of flow distribution in plate-type core affected by uneven inlet temperature distribution. (June 2016) - Xia, G.L.; Su, G.H.; Peng, M.J.
Highlights: Flow and power distribution of plate-type core are studied using RELAP5-3D code. Effect of uneven inlet temperature on flow distribution can be considered. Reactor power peaking factor shifts to low inlet temperature region. Flow peaking factor shifts to high inlet temperature region. Effect of uneven inlet temperature on flow distribution is much greater than power. Abstract: The flow and power distribution characteristics of plate-type fuel reactor core have been investigated in the present study. A reactor core thermal-hydraulic and neutronics coupled model was established using RELAP5-3D codes. The coupled modeling method was used to establish the thermo-hydraulic model, and the phenomenon of two-phase flow instability in a parallel two-channel system was used to verify the reliability of the method. Besides, the influence on power and flow distributions of uneven core inlet temperature was also studied by the application of coupled three-dimensional neutron-kinetics and thermal-hydraulics. The results show that, the coupled modeling method is reliable and can be used to establish the thermo-hydraulic model of a reactor core. By this method, both the effects of heating power and inlet temperature on flow distribution have been studied. The flow and power distributions of reactor core are inseparable and have a great effect on each other under the strong coupling of thermal-hydraulic and neutronics, but the non-uniformity of power distribution is greater than flow distribution. When reactor core inlet temperature distribution is uneven, reactor power peaking factor shifts to the low inlet temperature region, and flow peaking factor shifts to the high inlet temperature region. The effect of uneven core inlet temperature on flow distribution has a far greater impact than reactor power.